2021
DOI: 10.1002/ppp3.10199
|View full text |Cite
|
Sign up to set email alerts
|

Edible mycorrhizal fungi of the world: What is their role in forest sustainability, food security, biocultural conservation and climate change?

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 94 publications
0
28
0
2
Order By: Relevance
“…The harvest, use, and trade in wild fungi supports diverse Sustainable Development Goals and provides key provisioning ecosystem services such as food (SDG 2), medicines (SDG 3), and livelihoods (SDGs 1, 8, and 12; Figure 2) (Boa, 2008; Pérez‐Moreno et al., 2021a,b; Román et al., 2006). Globally, more than 2180 species of wild fungi are used for food (Li et al., 2021).…”
Section: Benefits Provided By Wild Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…The harvest, use, and trade in wild fungi supports diverse Sustainable Development Goals and provides key provisioning ecosystem services such as food (SDG 2), medicines (SDG 3), and livelihoods (SDGs 1, 8, and 12; Figure 2) (Boa, 2008; Pérez‐Moreno et al., 2021a,b; Román et al., 2006). Globally, more than 2180 species of wild fungi are used for food (Li et al., 2021).…”
Section: Benefits Provided By Wild Fungimentioning
confidence: 99%
“…The value of international trade in these species has been steadily increasing over the last 15 years, such that in 2019, it involved 134 countries and a trade value of over 5.2 billion US dollars (UN Comtrade Dataset) (de Frutos, 2020). The level of wild fungi use and trade varies widely by region, in some places representing the seasonal primary livelihood for rural people (Pérez‐Moreno et al., 2021a,b). It can be especially crucial for groups such as the elderly, the poor, and women, who may have few other livelihood options (Bonet et al., 2014).…”
Section: Benefits Provided By Wild Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Basidiomycota play a crucial role in terrestrial ecosystems, with members belonging to important trophic modes such as the saprotrophs, pathogens, or ectomycorrhizal fungi (EMF) [3,4]. Dominant in forest ecosystems, EMF regulate plant health, nutrient exchange, and forest sustainability [5,6]. Many studies in recent years have demonstrated important microbial interactions during the process of EMF development and establishment.…”
Section: Introductionmentioning
confidence: 99%
“…Some 56 species have been reported as regularly collected and eaten in at least 17 countries (e.g., several European countries, Russia, China, Central and South America, Africa), although these figures are probably underestimated because little information is available for the local consumption of many African species [19,26]. Indeed, a very recent account of edible mushrooms species at the global scale lists some 100 edible milkcaps [27]. Lactarius deliciosus, commonly called saffron milkcap, is particularly popular, especially in Europe.…”
Section: Introductionmentioning
confidence: 99%